2001
DOI: 10.1016/s0945-053x(01)00128-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple changes in gene expression in chronic human Achilles tendinopathy

Abstract: TMŽ . Atlas cDNA cell interaction arrays CLONTECH were used to examine degenerate tissue from four patients with Achilles tendon disorders, in order to identify changes in expression of genes important in cell᎐cell and cell᎐matrix Ž . interactions. The greatest difference between normal post-mortem and degenerate tissue samples was in the level of MMP-3 Ž . stromelysin mRNA, which was down-regulated in all the degenerate samples. Quantitative RT-PCR assay of RNA extracted from paired 'normal' and degenerate Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
215
5
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(237 citation statements)
references
References 21 publications
16
215
5
1
Order By: Relevance
“…The level of MMP activity in a tissue can be regulated by changes in gene expression, by the cleavage of latent MMP precursors, and by association of the MMP with inhibitory proteins (11). We have previously described differences in the expression of certain MMPs between normal and degenerate human tendons, consistent with a role in tendon pathology (12).…”
supporting
confidence: 69%
See 3 more Smart Citations
“…The level of MMP activity in a tissue can be regulated by changes in gene expression, by the cleavage of latent MMP precursors, and by association of the MMP with inhibitory proteins (11). We have previously described differences in the expression of certain MMPs between normal and degenerate human tendons, consistent with a role in tendon pathology (12).…”
supporting
confidence: 69%
“…Tendon pain and degeneration have been associated with an increase in the normal turnover of matrix proteins (9,10,12). MMP-3 has a broad substrate specificity; it is able to degrade matrix components including type III collagen and the proteoglycans aggrecan and versican, and is capable of activating a variety of other MMPs and pro-tumor necrosis factor (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…shown that a number of molecular changes occur within the diseased tendon, including altered content and expression of collagen and proteoglycan (PG) and expression of matrix-degrading enzymes (6)(7)(8)(9)(10)(11)(12)(13)(14). However, which if any of these changes precede and lead to rupture, and which are a consequence of tearing is unknown.…”
mentioning
confidence: 99%